Principal normal stress cavitation criterion for CFD analysis of loading capacity in journal bearings. Issue 9 (4th November 2019) - Li, Qiang; Zhang, Shuo; Wang, Yujun; Xu, Wei-Wei; Wang, Zengli; Wang, Zhenbo
Abstract : Purpose: Shear stresses have a considerable influence on the characteristics of lubricants and become significant at high rotating speeds. This study aims to investigate the influences of shear cavitation (SC) on loading capacity of journal bearings. Design/methodology/approach: A principal normal stress cavitation criterion based on the stress applied to flowing lubricant in journal bearings is developed and used to investigate SC in journal bearings. A computational fluid dynamic (CFD) model for calculating the loading capacity is established using this criterion. After validation with experimental results, the loading capacity is calculated under different conditions. Findings: The calculation results indicate that SC intensifies when viscosity, speed and eccentricity increase. Angle of loading capacity with SC is larger than that without SC. The magnitude of loading capacity with SC is smaller than that without SC due to the decrease in the ultimate pressure. In addition, the magnitude difference between the loading capacity with and without SC increases when viscosity, speed and eccentricity increases. Originality/value: Present research can provide some guidance for calculating the loading capacity when a journal bearing is operating at high speed or with a high viscosity lubricant.